Contribution of Ternary Reaction to Pd Sorption on MX-80 in Na-Ca-Cl Solution at High Ionic Strength - Shinya Nagasaki; Justin Riddoch; Joshua Racette (Science and Technology of Nuclear Installations)
In this study, we first examined the sorption of Pd on MX-80 in Na-Ca-ClO4 solution as a function of pHc (3–9) and ionic strength (0.1 M–4 M) and confirmed that the experimentally derived Kd values could be fitted by a 2-site protolysis nonelectrostatic surface complexation and cation exchange (2SPNE SC/CE) model using three binary surface complexation constants previously estimated. Then, we investigated the sorption of Pd on MX-80 in Na-Ca-Cl-ClO4 solution as a function of pHc (3–9) and Cl-/ClO4- molar concentration ratio (0–∞) at the ionic strength = 4 M. We found that the sorption of Pd on MX-80 in Na-Ca-Cl-ClO4 solution could be simulated only by the three binary and one ternary surface complexations (S-OH+Pd2++4Cl-↔S-OPdCl43-+H+). This suggests that the contribution of other ternary surface complexations such as ≡S-OH +  Pd2++xCl-↔ ≡S-OPdClxx-1-+H+ (x = 1, 2 and 3) to Pd sorption in Na-Ca-Cl-ClO4 solution with ionic strength = 4 M was negligibly small.